Citra Merek dan Kepercayaan terhadap Loyalitas Pengguna Jasa: Pelajaran dari Grapari Mataram - Iswanto, Dedy; Sudarta, Sudarta; Rachman, M. Taufik; Yunarni, Baiq Reinelda Tri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
A brand that has a lot of users even though the internet rates are quite expensive, if we look back from the meaning of the brand, where if a brand can meet consumer expectations or even exceed consumer expectations and provide quality assurance at every opportunity of use, and the brand is produced by the company with a reputation, consumers will be more confident in their choices and consumers will have confidence in the brand, like the brand and consider the brand as part of themselves. Thus, brand loyalty will be easier to establish and the company will have a brand name that has strong consumer loyalty. Research conducted by researchers is a quantitative approach with survey research methods. The research design used is a conclusive research that is causal (causal research), which aims to study the cause-and-effect relationship between the independent (free) variables and the dependent (dependent) variable. The population in this study are consumers who have used and / are currently using Telkomsel products from PT. Grapari Mataram. PT. It is hoped that Grapari Mataram will continue to innovate and always provide products that have high quality and at prices that are competitive with other products and excellent service is a need of its consumers, so that the big name and trust in consumers is maintained and with the expectations of consumers or customers. always loyal to the products offered by Telkomsel. Telkomsel through PT. Grapari Mataram always provides products and services that are competitive with the products of other cellular operators so that the good name and brand trust that Telkomsel has in the eyes of consumers remains embedded and is able to retain existing customers and be able to attract new potential customers. Because in essence, regardless of the type of business, it is still the consumer who determines the survival of the business.